Neuropathic pain develops normally in mice lacking both Nav1.7 and Nav1.8 - Stirling L Caroline; Levato Alessandra; Nassar Mohammed A; Wood John N (SAGE Publishing, 2005)
Abstract Two voltage gated sodium channel α-subunits, Nav1.7 and Nav1.8, are expressed at high levels in nociceptor terminals and have been implicated in the development of inflammatory pain. Mis-expression of voltage-gated sodium channels by damaged sensory neurons has also been implicated in the development of neuropathic pain, but the role of Nav1.7 and Nav1.8 is uncertain. Here we show that deleting Nav1.7 has no effect on the development of neuropathic pain. Double knockouts of both Nav1.7 and Nav1.8 also develop normal levels of neuropathic pain, despite a lack of inflammatory pain symptoms and altered mechanical and thermal acute pain thresholds. These studies demonstrate that, in contrast to the highly significant role for Nav1.7 in determining inflammatory pain thresholds, the development of neuropathic pain does not require the presence of either Nav1.7 or Nav1.8 alone or in combination.